Antecedents of E-Service Quality, Customer Satisfaction and Trust which Affects Customer Intention - Henry Utama Putra; Ferdi Antonio (Institute of Computer Science (IOCS), 2021)
This research aims to boarden the knowledge to get better insight to the most important dimensions from electronic service quality which plays a huge part on customer satisfaction, its trust and behavior, elaborate from initially terms of E-service quality in the SiCepat Express courier service application that will adding knowledge in the future regarding the use of applications in delivery service sector. From online survey data to 234 costumers that processed by SEM-PLS. It was indicates that these three elements from e-service quality, namely apps design, fulfillment and customer service had affect to whole e-service quality. These results showed that these three antecedents process, likewise to mediated variable, e-service quality had major and positive affect to customer satisfaction and trust. With strongest impact was fulfillment to customer service. Meanwhile, direct affect from customer satisfaction and trust was found very strong in e-service quality. It revealed that there's positive affect from customer satisfaction and trust to continuous usage intention and word of mouth, therefore this results has confirmed the theory of customer satisfaction and trust in the SiCepat Express courier service application. This research model is moderate predictive accuracy with medium predictive relevance so it can be expand in further research.